Accuracy and validity: Do instrumented treadmills stay in the running? - Van Alsenoy, K.; Thomson, A.; Burnett, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
L i e is known regarding the reliability and validity of kinetic and temporal variables recorded by the Zebris FDM-THC! instrumented treadmill in comparison to Pedar-X in-sole system. Twenty participants walked and ran three times on the Zebris treadmill, whilst wearing the same running shoes fitted with Pedar-X in-soles. Maximal vertical force, contact time, and flight time data from five consecutive left and right foot contacts were derived from both systems. Within- and between day reliability (ICC and SEM%), validity (95% limits of agreement) and smallest detectable differences (SDD) were calculated. Data presented indicates a trade off between accuracy and ease of use but support the use of the Zebris treadmill in clinical practice where baseline measurements and follow up assessment are commonplace.